Ethical Leadership with Both “Moral Person” and “Moral Manager” Aspects: Scale Development and Cross-Cultural Validation - Zhu, Weichun (Journal of business ethics, 2019)
The importance of ethical leadership in organizations has been increasingly recognized, especially as a shield against unethical employee behaviors and corporate misconducts. Ethical leadership has been theorized to include two aspects: “moral person” and “moral manager.” This conceptualization resonates well with Chinese teachings of Confucius on leadership and management—namely xiuji (cultivating oneself) and anren (bringing the good to others). Based on the theoretical framework of ethical leadership, we develop and validate a new ethical leadership measure (ELM). Through qualitative studies (i.e., face-to-face interviews, open-ended surveys, and literature review) and five quantitative studies, we establish the reliability and convergent, discriminant, and predictive validities of the ELM in a Chinese context. In addition, using a US sample, we find that the ELM has partial measurement invariance across Chinese and American contexts.